Ecosystem multifunctionality of coastal marshes is determined by key plant traits - Minden, Vanessa; Kleyer, Michael; Mason, Norman (Journal of vegetation science, 2015)
QUESTIONS: As biodiversity losses increase due to global change and human‐induced habitat destruction, the relationships between plant traits and ecosystem properties can provide a new level of understanding ecosystem complexity. Using a functional response–effect approach, we show that multiple components of the carbon cycle are determined by a few plant traits, which in turn are strongly affected by environmental conditions. LOCATION: Salt marshes, northwest Germany. METHODS: We explored responses of morphological, chemical and biomass‐related plant traits to environmental drivers and examined their effects on carbon cycle properties, i.e. above‐ground biomass, above‐ground net primary productivity and decomposition. The combined analysis between environmental parameters, functional traits and ecosystem properties used structural equation modelling (SEM). RESULTS: Important response and effect traits were leaf dry matter content (LDMC) and below‐ground dry mass (BDM, responding to groundwater level and salinity) and leaf C:N ratio (responding to inundation frequency). Inundation and salinity led to increased allocation to below‐ground biomass and salt stress adaptation in leaves, which translated into increased decomposition rates. Release from these abiotic controls resulted in standing biomass accumulation, which was controlled by LDMC and canopy height as key traits. CONCLUSIONS: These findings demonstrate the interacting effects of non‐consumable environmental factors and soil resources on morphological, chemical and biomass traits, which affected carbon cycle properties. Loss of species from the community has the potential to change the relationships between environment and vegetation‐based ecosystem properties and therefore elicit effects on the multifunctionality of the entire and adjacent ecosystems.